Siglec Ligands - Anabel Gonzalez-Gil; Ronald L. Schnaar (Cells, 2021)
A dense and diverse array of glycans on glycoproteins and glycolipids decorate all cell surfaces. In vertebrates, many of these carry sialic acid, in a variety of linkages and glycan contexts, as their outermost sugar moiety. Among their functions, glycans engage complementary glycan binding proteins (lectins) to regulate cell physiology. Among the glycan binding proteins are the Siglecs, sialic acid binding immunoglobulin-like lectins. In humans, there are 14 Siglecs, most of which are expressed on overlapping subsets of immune system cells. Each Siglec engages distinct, endogenous sialylated glycans that initiate signaling programs and regulate cellular responses. Here, we explore the emerging science of Siglec ligands, including endogenous sialoglycoproteins and glycolipids and synthetic sialomimetics. Knowledge in this field promises to reveal new molecular pathways controlling cell physiology and new opportunities for therapeutic intervention.